Impact of different hyperbaric storage conditions on microbial, physicochemical and enzymatic parameters of watermelon juice - Pinto, Carlos (2022)
Hyperbaric storage (HS) of raw watermelon juice, up to 10days at 50, 75, and 100MPa at variable/uncontrolled room temperature (18-23°C, RT) was studied and compared with storage at atmospheric pressure (AP) under refrigeration (4°C, RF) and RT, being evaluated microbiological (endogenous and inoculated), physicochemical parameters, and enzymatic activities. Ten days of storage at 50MPa resulted in a microbial growth evolution similar to RF, while at 75/100MPa were observed microbial load reductions on endogenous and inoculated microorganisms (Escherichia coli and Listeria innocua, whose counts were reduced to below the detection limit of 1.00 log CFU/mL), resulting in a shelf-life extension compared to RF. The physicochemical parameters remained stable at 75MPa when compared to the initial raw juice, except for browning degree that increased 1.72-fold, whilst at 100MPa were observed higher colour variations, attributed to a lycopene content decrease (25%), as well as reductions on peroxidase residual activity (16.8%) after 10days, while both polyphenol oxidase and pectin methylesterase residual activities were similar to RF. These outcomes hint HS as a reliable alternative to RF as a new food preservation methodology, allowing energy savings and shelf-life extension of food products. This is the first paper studying the effect of HS on inoculated microorganisms and on a broad number of physicochemical parameters and on endogenous enzymatic activities, for a preservation length surpassing the shelf-life by RF.